2016
DOI: 10.1155/2016/8594087
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of File Size and Type and Irrigation Solutions on the Accuracy of Electronic Apex Locators: AnIn VitroStudy on Canine Teeth

Abstract: Measurements of the root canal during endodontic treatment have a significant influence on the course of the therapeutic process as well as on its final result in both human and veterinary medicine. The apical constriction should be the termination point for the preparation and filling of the root canal. This research was conducted with the use of a Septodont kit consisting of a small chamber filled with the examined solution in which a healthy second incisor was placed. The step back method was applied for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…wherein both 2% and 5.25% NaOCl gave the most favorable results with the use of both stainless steel and nickel-titanium files. [ 12 ] Intragroup comparison among irrigants in decreasing order was as follows: OCT >CHX >NaOCl >heated NaOCl. Similar result has been reported in a recent study by Altunbaş et al ., where least accurate results were found in the presence of NaOCl in teeth with perforation when using Dentaport ZX.…”
Section: Discussionmentioning
confidence: 99%
“…wherein both 2% and 5.25% NaOCl gave the most favorable results with the use of both stainless steel and nickel-titanium files. [ 12 ] Intragroup comparison among irrigants in decreasing order was as follows: OCT >CHX >NaOCl >heated NaOCl. Similar result has been reported in a recent study by Altunbaş et al ., where least accurate results were found in the presence of NaOCl in teeth with perforation when using Dentaport ZX.…”
Section: Discussionmentioning
confidence: 99%
“…Electronic measurements of working length may be influenced by different factors . Apex locators are frequently used with smaller size files, however, the effect of file size on measurement accuracy are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Enlargement of the root canal was initially performed using Gates Glidden burs, creating a glide path allowing the file to reach the apical foramen easily and directly, ensuring accuracy of the EAL readings . Sodium hypochlorite was used as the irrigant of choice as it has been found to not influence the accuracy of EALs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It comes from the fact that it is a solution characterized by high electrical conductivity and with the potential to penetrate into dentinal tubules and decrease electrical impedance of the root canal walls as well as generate better electrical contact with periapical tissues (13,18) Recent studies reported that some physico-chemical properties of root dentin can be affected by sodium hypochlorite solution. Hence, it is possible that such change has influenced the accuracies of the devices in present study (19)(20)(21) . Hence, NaOCl was used in different roots rather than those of CHX in order to avoid its effect on root dentin.…”
Section: Resultsmentioning
confidence: 95%